2014
DOI: 10.1080/00221325.2014.976535
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Control and Moral Emotions: Relations to Reparation in Early and Middle Childhood

Abstract: This study examined links between inhibitory control, moral emotions (sympathy and guilt), and reparative behavior in an ethnically diverse sample of 4- and 8-year-olds (N = 162). Caregivers reported their children's reparative behavior, inhibitory control, and moral emotions through a questionnaire, and children reported their guilt feelings in response to a series of vignettes depicting moral transgressions. A hypothesized meditation model was tested with inhibitory control relating to reparative behavior th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 48 publications
2
27
0
7
Order By: Relevance
“…While previous research has shown a positive correlation between 4-and 8-year-old children's negative emotion attribution in the happy victimizer task and caregiver-rated inhibitory control (Colasante et al, 2014), such correlational studies can only be suggestive of underlying causal relationships. Thus, we believe that the experimental approach with the direct manipulation of cognitive demands, as adopted in the current study, can add a more detailed understanding of how specific cognitive abilities affect moral emotion attribution.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…While previous research has shown a positive correlation between 4-and 8-year-old children's negative emotion attribution in the happy victimizer task and caregiver-rated inhibitory control (Colasante et al, 2014), such correlational studies can only be suggestive of underlying causal relationships. Thus, we believe that the experimental approach with the direct manipulation of cognitive demands, as adopted in the current study, can add a more detailed understanding of how specific cognitive abilities affect moral emotion attribution.…”
Section: Discussionmentioning
confidence: 90%
“…Previous research indicated young children's difficulty with attributing negative emotions to the violator of a moral norm in the happy victimizer task might at least be partly due to their limited cognitive abilities (e.g., Colasante et al, 2014;Gummerum et al, 2013;Krettenauer et al, 2008). While previous research has shown a positive correlation between 4-and 8-year-old children's negative emotion attribution in the happy victimizer task and caregiver-rated inhibitory control (Colasante et al, 2014), such correlational studies can only be suggestive of underlying causal relationships.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, the effects of resting HR may be more susceptible to moderation by guilt and sympathy in older children if temperamental variables give way to increasing social‐emotional factors (and therefore have a lesser impact on social behavior over time; Bates, ). For empirical support of this theorizing, see Colasante, Zuffianò, Bae, and Malti ().…”
Section: Introductionmentioning
confidence: 91%